Technology Enabled Political Communication in Social Networking Sites: Recent trends in the Literature - Darshan B.M; Ramya K Prasad (International Journal of Advanced Science and Technology, 2020)
The social media has significantly reshaped domains and nature of political communication. It is emerged as complementary and alternative to the mainstream media and communication techniques. The greater accessibility, availability and easiness of usage has made social media a popular intermediate for political communication. The present paper explores the recent trends in political communication using the social media field with the purpose of formulating a novel design for an empirical investigation in the Indian context. The researchers have used secondary data sources to conduct a qualitative analysis on technology enabled Political Communication in Social Networking Sites. The review and analysis of published evidence were insightful in extracting the research gaps in the field of study.